The (Trans)Formation of Religious Capital in Indonesian Politics During New Order Era: A Case Study of Nahdlatul Ulama - Damm, Muhammad R. (Journal of Indonesian Social Sciences and Humanities, 2018)
Religious capital always has a crucial role in Indonesian politics. This paper aims to analyze the formation of religious capital in the New Order era that has been heavily influenced by the dynamics of the relationship between the state and religious groups, especially Islam, over time. As a case study, this paper will discuss Nahdlatul Ulama (NU). By analyzing the development of NU during the course of the New Order, it shows that the formation of religious capital was affected by the New Order’s systematic attempts to contain Islamic forces. Since the late 1960s until the midst of 1980s, the New Order orchestrated a systematic weakening of Islamic movement through destabilization and demonization of the Muslim community. It also attempted systematically to reduce the political power of Islamic elements by sanctioning several policies and regulations, especially simplification of the political party system in 1973 and the enforcement of Pancasila as the sole principle for socio-political life in 1985. In 1984 NU declared its resolution to return to its original status as religious-based social organization, adopted Pancasila as its principle, and formally retreated from politics. However, in the late 1980s and during 1990s, although institutionally experienced de-politicization, NU proved to remain significant in the political landscape. From this analysis, it is apparent that NU’s religious capital comprised of some ingredients: the centrality of ulama, the importance of securing NU community’s interests, and the necessity of resources obtained through a good relationship with the state.